Simultaneous Determination of A Novel Antitrypanosomal Compound (OSU-36) and its Ester Derivative (OSU-40) in Plasma by HPLC: Application to First Pharmacokinetic Study in Rats - Pavel Gershkovich; Kishor M. Wasan; Olena Sivak; Summer Lysakowski; Carolyn Reid; Kokku Premalatha; Karl A. Werbovetz (Frontiers Media S.A., 2011)
Purpose. To develop an HPLC-UV method for determination of a novel antitrypanosomal compound (OSU-36) and its ester prodrug (OSU-40) in rat plasma and to apply the method for pharmacokinetic evaluation of both compounds in rats. Methods. Since an attempt to assay for OSU-36 and OSU-40 in non-stabilized plasma resulted in highly non-linear calibration curves and poor sensitivity due to instability of the compounds, the plasma was stabilized using paraoxon and ascorbic acid. The sample treatment included protein precipitation by acetonitrile; evaporation; reconstitution with acetonitrile and filtration. The chromatography conditions included Xterra RP18 3.5µm 4.6X100mm column and gradient mobile phase system of acetonitrile-water. Results. The limits of quantification (LOQ) were 50 ng/mL and 40 ng/mL for OSU-36 and OSU-40, respectively. The intra- and interday precision and accuracies were below 13% for low, medium and high quality control samples for both compounds. While OSU-40 has been stable in all tested handling conditions, OSU-36 was unstable in plasma after 20 days storage in -80°C or 4h 28°C storage. The developed method has been applied for a pharmacokinetic study in rats which revealed that an ester prodrug OSU-40 is rapidly converted to OSU-36 within the plasma compartment by plasma esterases. OSU-36, in turn, relatively quickly undergoes oxidative metabolism, including within the plasma compartment. Conclusions. A supplementation of rat plasma with an esterase inhibitor to prevent degradation of ester prodrug (OSU-40), and with antioxidant to prevent oxidation of OSU-36, is necessary for reliable determination of both compounds. Due to limited stability of OSU-36 in stabilized rat plasma, long-term storage of samples or prolonged handling in room temperature conditions is not recommended.